Proceedings of the 2009 International Conference on Computer-Aided Design 2009
DOI: 10.1145/1687399.1687412
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced reliability-aware power management through shared recovery technique

Abstract: While Dynamic Voltage Scaling (DVS) remains as a popular energy management technique for real-time embedded applications, recent research has identified significant and negative impact of voltage scaling on system reliability. For this reason, a number of reliability-aware power management (RA-PM) schemes were recently proposed to preserve the system reliability when DVS is used. In this paper, we propose a new approach, called the shared recovery (SHR) technique, to minimize the system-level energy consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 31 publications
(64 reference statements)
1
46
0
Order By: Relevance
“…We focus only on transient faults as it has been observed that transient faults are the major source of concern in safetycritical applications [27][29] [31]. In this paper, we consider frame-based real-time applications [29][31] with hard timing constraints where a set of dependent tasks, e.g., Γ={T 1 , T 2 , T 3 , …, T n }, is executed within each frame and must be completed before the end of the frame (deadline) [31]. The LESS system does not need any dedicated scheduler.…”
Section: Proposed Low-energy Standby-sparing Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…We focus only on transient faults as it has been observed that transient faults are the major source of concern in safetycritical applications [27][29] [31]. In this paper, we consider frame-based real-time applications [29][31] with hard timing constraints where a set of dependent tasks, e.g., Γ={T 1 , T 2 , T 3 , …, T n }, is executed within each frame and must be completed before the end of the frame (deadline) [31]. The LESS system does not need any dedicated scheduler.…”
Section: Proposed Low-energy Standby-sparing Techniquementioning
confidence: 99%
“…Note that, as discussed in Section II, here we focus only on transient faults. The occurrence of transient faults in digital systems usually follows a Poisson process [6][7] [29]. It has been observed that in DVS-enabled systems the rate of transient faults increases exponentially as the supply voltage decreases, so that the fault rate can be expressed as [32]: …”
Section: Reliability Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The recovery job is executed at the maximum speed only when its scaled primary job incurs transient faults. The shared-recovery based RAPM scheme has also been studied where several tasks with scaled frequencies may share one recovery task for reliability preservation [22]. More recently, considering such negative effects of DVS on system reliability, the recovery allowance based scheme that can achieve arbitrary reliability levels for each periodic task is further studied [23].…”
Section: Closely Related Workmentioning
confidence: 99%
“…Perfect fail-silent behavior is one assumption that is often used in literature. It is assumed that all faults are detected within a certain time interval and the fault-detection overhead is contained in the tasks' WorstCase Execution Times (WCETs), e.g., in fault-tolerant task scheduling [8,15,4,17,6,5], in reliability-aware energy management [16,20,22] and in error-aware system design [9,10]. With this assumption, each task will produce either a correct output or no output at all.…”
Section: Introductionmentioning
confidence: 99%